The Role of Fulfilling Affiliation Needs as a Mediator of the Effect of E-Learning Learning Model Experience on Student Motivation in Makassar City - Tetteng, Basti; Dewi, Eva Meizara Puspita; Sulastri, Tri (Indonesian Journal of Educational Studies, 2023)
The purpose of this study was to determine the role of fulfilling affiliation needs as a mediator of the effect of E-Learning learning model experience on learning motivation in public high school students in Makassar City. The research sample collection technique used Multistage Cluster Random Sampling. The research data collection technique used (1) User experience questionnaire (UEQ) to measure the experience of E-Learning learning model. (2) Interpersonal orientation scale (IOS) to measure the fulfilment of students' affiliation needs. And (3) Learning Motivation Scale to measure students' learning motivation. The research data analysis technique used descriptive analysis and hypothesis testing. The results of the research data analysis showed (1) There is a very significant effect of e-learning experience on affiliation needs (β = 0.476; p < 0.001), (2) There is a very significant effect of affiliation needs on learning motivation (β = 0.336; p < 0.001), (3) There is a very significant effect of e-learning experience on learning motivation (β = 0.378; p < 0.001). (4) There is a highly significant role of affiliation needs as a mediating influence of e-learning experience on learning motivation (β = 0.160; p < 0.001).